MEMBENTUK KARAKTER PELAJAR BEBAS NARKOBA DI SMPN 2 SINTANG - Suseka, Septha; Fingky, Winarto; Anjela, Tersia (STKIP Persada Khatulistiwa Sintang, 2024)
The purpose of this article is to provide an overview of the phenomenon of drug abuse among teenagers and the efforts made to prevent it. This study was conducted with a qualitative approach and is descriptive in nature. Meanwhile, there are several steps that need to be taken to deal with the problem of drug abuse among teenagers. This includes prevention and education, anti-drug campaigns, and massive enforcement actions starting from families, schools, and communities. Therefore, parents must act democratically by treating their children or teenagers well and giving them enough attention. To prevent drug abuse among teenagers, schools must provide education and various information about the dangers of drugs. In society, every member of society must act firmly and consistently as social control to prevent drug abuse. The research results show that drugs have spread in Indonesia today, especially among teenagers. There is already a drug emergency in Indonesia, and everyone must pay attention to this. Meanwhile, there are several steps that need to be taken to deal with the problem of drug abuse among teenagers. This includes prevention and education, anti-drug campaigns, and massive enforcement actions starting from families, schools, and communities. Therefore, parents must act democratically by treating their children or teenagers well and giving them enough attention. To prevent drug abuse among teenagers, schools must provide education and various information about the dangers of drugs. In society, every member of society must act firmly and consistently as social control to prevent drug abuse.Keywords: Preventing Drug Abuse, Drug Abuse, Teenager